• Revision:Indices and Surds

TSR Wiki > Study Help > Subjects and Revision > Revision Notes > Mathematics > Indices and Surds

Indices are used to describe the general term for ^2 in say  x^2 . There are a few laws to know when manipulating expressions involving indices.


Laws of Indices

 a^m \times a^n = a^{m+n}

 a^m \div a^n = a^{m-n}

 (a^m)^n = a^{mn}

 a^{\frac{1}{m}} = \sqrt[m]{a}

 a^{-m} = \frac{1}{a^m}

 a^{\frac{m}{n}} = \sqrt[n]a^m

 a^0 = 1


 \sqrt[5]4^3 = (4^3)^{\frac{1}{5}} = (4^{\frac{3}{5}})

 5^3 \times 5^4 = 5^7

 \frac{5^5}{5^2} = 5^{3}


Surds are basically an expression involving a root, squared or cubed etc...

There are some basic rules when dealing with surds

 \sqrt{a} + \sqrt{a} = 2\sqrt{a}

 6\sqrt{a} - 2\sqrt{a} = 4\sqrt{a}

 \sqrt{a} \times \sqrt{b} = \sqrt{ab}

 \sqrt{\frac{a}{b}} = \frac{\sqrt a}{\sqrt b}

Also notice the special case

 \sqrt{a} \times \sqrt{a} = a^{\frac{1}{2}} \times a^{\frac{1}{2}} = a

Difference of Two Squares

 x^2 - y^2 = (x + y)(x - y) This is called the difference of two squares

Rationalising Surds

When you have a fraction where both the nominator and denominator are surds, rationalising the surd is the process of getting rid of the surd on the denominator.

To rationalise a surd you multiply top and bottom by fraction that equals one. Take the example shown below


To rationalise this multiply by effectively 1

 \frac{1}{\sqrt2} \times \frac{\sqrt 2}{\sqrt{2}}

Can you see why  \frac{\sqrt2}{\sqrt{2}} was chosen? This is because  \sqrt{2} \times \sqrt{2} = 2 so the denominator becomes surd free.

For a more complex term

 \frac{1+\sqrt{2}}{1 - \sqrt{5}}

First of all, we need to get rid of the surd expression on the bottom, you should remember the difference of two squares formula.

 a^2 - b^2 = (a + b)(a - b)

suppose a = 1 and b =  \sqrt{5}

 1^2 - 5 = (1+\sqrt{5})(1 - \sqrt{5}) = -4

So to get rid of the denominator surd we multiply  \frac{1+\sqrt{2}}{1 - \sqrt{5}} by  \frac{{1+\sqrt{5}}}{1+\sqrt{5}} like so.

 \frac{1+\sqrt{2}}{1 - \sqrt{5}} \times \frac{{1+\sqrt{5}}}{1+\sqrt{5}}

 = \frac{(1+\sqrt{2})(1+\sqrt{5})}{(1-\sqrt{5})(1+\sqrt{5})}

 = \frac{1 + \sqrt{5} + \sqrt{2} + \sqrt{10}}{1^2 - 5}

 = -\frac{1}{4} - \frac{\sqrt5}{4} - \frac{\sqrt2}{4} - \frac{\sqrt10}{4}

In general

  • Fractions in the form  \sqrt{\frac{1}{a}} multiply top and bottom by  \sqrt{a}
  • Fractions in the form  \frac{1}{a + \sqrt{b}} multiply the top and bottom by  a - \sqrt{b}
  • Fractions in the form  \frac{1}{a - \sqrt{b}} multiply the top and bottom by  a + \sqrt{b}
Try Learn together, TSR's study area

revision notes




a study planner

of discussions

Today on TSR
Does your body insecurities make you avoid PE or exercise?
Study resources

The Student Room, Get Revising and Marked by Teachers are trading names of The Student Room Group Ltd.

Register Number: 04666380 (England and Wales), VAT No. 806 8067 22 Registered Office: International House, Queens Road, Brighton, BN1 3XE